2018
DOI: 10.1111/ijfs.14007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activity and potential of heather (Erica spp.) extracts in the control of Listeria monocytogenes

Abstract: Summary In this work, heather and its flowers were studied regarding their antioxidant and antimicrobial activities. Plants were subjected to ultrasound‐assisted methanolic extraction followed by fractionation. A phytochemical characterisation of extracts content in total phenols and flavonoids, and their antioxidant activity was performed. The antimicrobial activity was evaluated through the determination of minimum inhibitory concentration and by bioautography. Following, studies on the antilisterial potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…As a result shown in Table 2, no significant differences were observed between the SS, PVC, and PC surfaces. Similarly, Santos et al (2018) showed that all The microscopic observations performed for L. monocytogenes 32 biofilms showed a dense three-dimensional structure in all surfaces (Figures 3a-5a), similar to the reports of other authors (Borucki et al, 2003;Dubravka et al, 2009). Using the scanning electron microscope, we established that L. monocytogenes 32 formed strong biofilm and that individual bacterial cells adsorbed to all three surfaces.…”
Section: Determination and Visualization Of The Biofilm And Anti-bisupporting
confidence: 87%
See 2 more Smart Citations
“…As a result shown in Table 2, no significant differences were observed between the SS, PVC, and PC surfaces. Similarly, Santos et al (2018) showed that all The microscopic observations performed for L. monocytogenes 32 biofilms showed a dense three-dimensional structure in all surfaces (Figures 3a-5a), similar to the reports of other authors (Borucki et al, 2003;Dubravka et al, 2009). Using the scanning electron microscope, we established that L. monocytogenes 32 formed strong biofilm and that individual bacterial cells adsorbed to all three surfaces.…”
Section: Determination and Visualization Of The Biofilm And Anti-bisupporting
confidence: 87%
“…Similarly, Santos et al. (2018) showed that all concentrations tested a fraction of heather extracts led to statistically significant inhibition of biofilm formation of L. monocytogenes , with inhibition percentages as high as 91%. Overall, L. plantarum ‐derived CFE with its sub‐MIC values was found to be effective on all surfaces which are all resistant to acid and other sanitizer treatments (van der Veen & Abee, 2011) that makes routine disinfection in the food industry more difficult.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Since ancient times, Erica species have been used as a traditional medicine for the treatment of burns and wounds by the local people in Anatolia. The studies have been showed that Erica species possess antiulcer [8,9], antimicrobial [10,11], antibacterial, cytotoxic [12][13][14][15] and antioxidant [16][17][18][19][20] activities. It has also been reported that Erica species have (poly) phenolic, flavonoid, coumarin and triterpenoid, compounds [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to our findings. C. vulgaris has many phenolic compounds with antioxidant activity, which could explain the high activity of its extracts [ 31 , 49 ]. Even C. vulgaris honey has antioxidant activities [ 50 ].…”
Section: Discussionmentioning
confidence: 99%